A First Estimate of Species Diversity for Benthic Diatom Assemblages from the Revillagigedo Archipelago, Mexico - David A. Siqueiros Beltrones; Francisco Omar López-Fuerte; Yuriko Jocselin Martínez; María del Carmen Altamirano-Cerecedo (Diversity, 2021)
Recent investigations at previously unexplored localities on the Mexican coast have confirmed the high taxonomic potential of benthic marine diatom assemblages (BMDA) in the region. An exploratory study of epiphytic diatoms of macroalgae in the Revillagigedo Archipelago (RA) suggested that further studies would yield many more taxa, prompting the hypothesis that diversity measurements, based on ecological indices, would be among the highest in pristine environments. Thus, the aim of this research was to enrich the record of epiphytic diatom floristics of the RA, and to estimate species diversity based on information theory (H′). Floristically, 167 identified taxa are added here to the BMDA species list of the RA, bringing the total to 397 taxa overall, including 52 taxa that are potentially new records for the Mexican Pacific coast. Among the most conspicuous genera are Mastogloia with five new taxa and it remains the most diverse genus with 55 taxa overall, followed by Cocconeis (27), Nitzschia (24), Amphora (23), Navicula (19), Diploneis (17) and Grammatophora (15). As expected for a pristine environment, the computed species diversity values for the BMDA were high, ranging from H′ = 3.92–5.2, depicting stability. Future surveys are expected to further increase the species richness of BMDA for the RA.